2022
DOI: 10.1108/gs-05-2022-0049
|View full text |Cite
|
Sign up to set email alerts
|

Grey system theory in sustainable development research—a literature review (2011−2021)

Abstract: PurposeAs the grey systems theory has been widely used in the field of sustainable development (SD) research, in the following, a short literature overview will be put forward, starting from the usage of these theories in the economic development, social inclusion and environmental protection contributions to the evolving process of SD during 2011–2021. The purpose of this paper is to identify some key studies from all the SD areas in which the grey systems can be used in order to open and to bring the researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 98 publications
0
10
0
Order By: Relevance
“…, 2022; Tao et al. , 2022), management, sustainable development (Hu and Liu, 2022), agricultural science (Li et al. , 2022) and many others.…”
Section: Methodological Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2022; Tao et al. , 2022), management, sustainable development (Hu and Liu, 2022), agricultural science (Li et al. , 2022) and many others.…”
Section: Methodological Proceduresmentioning
confidence: 99%
“…Given the prevalence of uncertain systems with small samples and limited information worldwide, GS 14,1 this method proves highly effective and widely applicable (Liu et al, 2022b;Prakash et al, 2023). Thus, as argued by Li et al (2022), the emergence and development of grey systems theory has caused innovation and progress across several research areas, including engineering Tao et al, 2022), management, sustainable development (Hu and Liu, 2022), agricultural science (Li et al, 2022) and many others.…”
Section: Use Of Ahp and Grey Fixed Weight Clusteringmentioning
confidence: 99%
“…In such scenarios, the grey system theory proves to be highly advantageous. It stands out in handling situations with inadequate information and dealing with uncertain problems (Liu et al ., 2017, 2022; Hu and Liu, 2022; Liu et al ., 2022a, b; Tao et al. , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…In such scenarios, the grey system theory proves to be highly advantageous. It stands out in handling situations with inadequate information and dealing with uncertain problems Hu and Liu, 2022;Liu et al, 2022a, b;Tao et al, 2022). The grey clustering model is one of the evaluation methods and has a wide range of applications (Delcea et al, 2022;He et al, 2022;Karimi and Yahyazade, 2022;Li et al, 2022;Luo et al, 2022;Liu et al, 2022a, b) In this stage, a grey clustering model based on mixed end-point possibility function is applied to evaluate the quality risk of systems.…”
Section: Stage 1: Establish Phfs-qfd Platform To Identify Quality Ris...mentioning
confidence: 99%
“…Also, Hu et al [57] and Javanmardi et al [58] reported that GRA is very suitable in its application to solve sustainable development issues. Muhammad Muneeb et al [59] proposed a case study of the Pakistan telecommunication industry for achieving SDGs using GRA.…”
Section: Grey Rational Analysismentioning
confidence: 99%